Grain yield performance and flowering synchrony of CIMMYT’s tropical maize (Zea mays L.) parental inbred lines and single crosses - Worku, Mosisa; Makumbi, Dan; Beyene, Yoseph; Das, Biswanath; Mugo, Stephen; Pixley, Kevin; Ba¨nziger, Marianne; Owino, Fidelis; Olsen, Michael; Asea, Godfrey; Prasanna, Boddupalli M. (Euphytica, 2016)
Maize production constraints in sub-Saharan Africa (SSA) are being addressed by CIMMYT and partners through an array of projects, focusing on developing and evaluating parental inbred lines and single-crosses as well as formulating, evaluating and releasing high-yielding and stress resilient hybrids adapted to different agro-ecologies. The objectives of the present study were to (1) evaluate the grain yield performance of parental elite inbred lines developed over the years, and single crosses; and (2) ascertain the flowering synchrony among inbred lines and singlecross hybrid parents. Parental inbred lines and singlecrosses were evaluated at seven locations in two countries in 2014. Combined analysis of variance revealed differences (P\0.01) among genotypes for grain yield (GY) and among different years/era of release of the inbred lines. The improvement in GY of inbred lines was estimated to be 1.4 %per year. Under irrigated conditions GY of some single-cross hybrids was over 16 t ha-1. Some single-cross and inbred line parents showed acceptable flowering synchrony, good producibility, and stable performance across testing environments, suggesting that these have high potential for seed production. Further research is needed to determine the physiological and morphological characteristics that contributed to the GY improvement in the parental inbred lines. Information generated from this study will enhance the use of CIMMYT’s tropical mid-altitude parental germplasm by breeders working in both private and public breeding programs for developing and deploying high-yielding maize hybrids for the benefit of small-scale farmers in SSA.
Keywords: Flowering synchrony; Inbred lines; Maize; Single cross hybrids; Three-way cross hybrids